Mokslinėje veikloje dalyvaujančių studentų informacinio aprūpinimo klausimu - Dagytė, Ina (Knygotyra, 1988)
Students are part of the scientific research workforce in higher education institutions. The structure of scientific resources consists of scientists, material and technical devices, and information services. The information services for students are a component of the overall information services for scientific research. The development of students' information needs and their experiences with bibliographic work are emphasized. Two key functions of the information work performed by students are highlighted.